PROTECTIVE EFFECT OF COMBINATION OF ETHANOLIC EXTRACTS OF XIMENIA AMERICANA AND TERMINALIA MACROPTERA AGAINST ALCOHOL-INDUCED HEPATOTOXICITY IN RATS - BALLO, Mahamadou; BAH, Sekou; ESTELLE NH YOUL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of this study was to evaluate the hepatoprotective effect of the combination. Methods: Serum liver markers, tissue antioxidant activity, and histological changes in the livers of rats from the blank, negative (distilled water), positive (silymarin 100 mg/kg bw), and test (combination 500 mg/kg bw) groups were measured after 7 days of pretreatment and induction of hepatotoxicity by 10 g/kg bw alcohol every 12 h for 48 h. Results: Rats in the negative control group showed a highly significant (p<0.001) increase in aspartate aminotransferase (AST), alanine aminotransferase (ALT), and total bilirubin (BT) levels by 281.13%, 221.7%, and 93.44%, respectively, compared to rats in the blank group. Pretreatment with the combination resulted in a highly significant (p<0.001) decrease in AST, ALT, and BT levels of 69.19%, 62.24%, and 41.52%, respectively. The study of tissue oxidative stress parameters revealed a very significant (p<0.01) increase in superoxide dismutase (123.08%), glutathione (131.66%), and catalase (49.01%) activities and a significant (p<0.05) decrease in malondialdehyde concentration (59.72%) in the group pretreated with the combination compared with the negative control group. Steatosis and necrosis estimated at 50% were observed in rats in the negative control group. In contrast, necrosis observed in the group pre-treated with the combination was <10%. Conclusion: These data suggest that the combination is effective in preventing the elevation of biochemical markers and the imbalance of enzymatic and non-enzymatic antioxidant systems caused by alcohol.